A review and perspectives on predicting the performance and durability of electrical contacts in automotive applications. (March 2021) - Kloch, Konrad T.; Kozak, Pawel; Mlyniec, Andrzej
Highlights: Automotive electrical contacts and connector failure causes are presented. The most important factors affecting durability of electrical connectors are discussed. The micro-scale and macro-scale approaches to durability modelling are compared. Future research directions necessary to develop predictive models are indicated. Abstract: This review reports the recent progress in predicting the performance and long-term durability of electrical connectors in the automotive industry. The review features a short introduction to electrical contacts as well as the validation process before product launch, followed by a study of fretting wear and the latest mathematical models describing this phenomenon. We discuss approaches to numerical modeling in the micro- and macro-scale, including the identification of the most promising research approaches to allow durability prediction of an electrical connector. Finally, we address some gaps in the research which require further investigation. This would allow further development of numerical models enabling the prediction of automotive connector durability with regard to its electrical and mechanical performance, and hence, the performance of the entire wire harness.